Migration in sub-Saharan Africa - Adepoju, Aderanti; Nordiska Afrikainstitutet (Uppsala : Nordiska Afrikainstitutet, 2008)
Africans arriving by rickety fishing boats to the Canary Islands, risking the passage across the Straits of Gibraltar or washed up on the Italian island of Lampedusa are familiar examples of the recent growth in migration from Africa to Europe. There is a dark side of migration in human trafficking, but the picture of a continent on the move also includes highly skilled professionals from Nigeria and Ghana who seek employment in universities and other professions in South Africa. On the positive side migrant remittances are a major source of income in many sub-Saharan African countries, helping to sustain the lives of poor home communities. A major challenge now facing sub-Saharan Africa is how to attract skilled emigrants back for national development.
1. Why focus on migration? -- 2. The sub-Saharan African migration scene -- 3. Emigration of professionals : causes and consequences -- 4. The characteristics and roles of remittances in sub-Saharan Africa -- 5. The role of the diaspora in country-of-origin development -- 6. Human trafficking -- 7. Legislative framework governing migration in sub-Saharan Africa -- 8. Principal actors in migration issues in sub-Saharan Africa -- 9 . Migration and development : challenges and prospects.
Includes bibliographical references (p. 60-68).
Keywords: Urbanisation -- Africa, Sub-Saharan.; Rural-urban migration -- Africa, Sub-Saharan.; Population policy -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Emigration and immigration